OPTIMAL CROSS-SECTIONAL DESIGN FOR MINIMUM EMBODIED ENERGY - Gil Martin, Luisa Maria; Hernández Montes, Enrique (Journal of Applied Engineering Science, 2014)
In order to reduce the CO2 emission engineers and architects must optimize the use of materials, particularly steel, making an optimal use of it. It is possible to guarantee the strength of the structural element reducing the amount of steel locating it properly at the cross-section and introducing a higher control level at construction site.
Keywords: Saving of steel; Embodied Energy; Sustainable construction